2009
DOI: 10.1098/rstb.2008.0284
|View full text |Cite
|
Sign up to set email alerts
|

Transport and release of chemicals from plastics to the environment and to wildlife

Abstract: Plastics debris in the marine environment, including resin pellets, fragments and microscopic plastic fragments, contain organic contaminants, including polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons, petroleum hydrocarbons, organochlorine pesticides (2,2 0 -bis(p-chlorophenyl)-1,1,1-trichloroethane, hexachlorinated hexanes), polybrominated diphenylethers, alkylphenols and bisphenol A, at concentrations from sub ng g -1 to mg g -1. Some of these compounds are added during plastics manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
1,288
2
73

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 2,371 publications
(1,380 citation statements)
references
References 96 publications
17
1,288
2
73
Order By: Relevance
“…Further research has shown that plastic debris sorb, concentrate and transport POPs in the marine environment that can subsequently be ingested by marine organisms (Teuten et al, 2009;Zarfl and Matthies, 2010;Browne et al, 2013;Schirinzi et al, 2016). However, little is known about pollutant's desorption rate during digestive processes hence chemicals' potential ability to accumulate in tissue and organs and disrupt key ecophysiological processes in organism of ecological relevance (Bakir et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Further research has shown that plastic debris sorb, concentrate and transport POPs in the marine environment that can subsequently be ingested by marine organisms (Teuten et al, 2009;Zarfl and Matthies, 2010;Browne et al, 2013;Schirinzi et al, 2016). However, little is known about pollutant's desorption rate during digestive processes hence chemicals' potential ability to accumulate in tissue and organs and disrupt key ecophysiological processes in organism of ecological relevance (Bakir et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…If microplastic densities continue to increase, then substrate-associated biota such as H. sericeus may be expected to increase as well, potentially at the expense of prey such as zooplankton or fish eggs [3,4]. Future work should incorporate the dynamics of substrate-associated assemblages with ongoing work in toxicology [17], microbial ecology [21] and faunal interactions [13][14][15][16] to provide a better understanding of the impact of microplastic pollution on pelagic marine ecosystems. …”
Section: Discussionmentioning
confidence: 99%
“…68 Em todos esses ambientes estão presentes itens grandes (inteiros ou fragmentados), facilmente identificáveis, mas a atenção tem atualmente se voltado para as frações menores, possivelmente mais danosas à fauna e flora marinhas, que são os microplásticos. 78,79 Os microplásticos (< 5 mm) em ambientes marinhos têm recebido bastante atenção da comunidade cientifica na última década, 50,78 tendo inclusive merecido mais de uma dúzia de revisões da literatura (considerando-se apenas os artigos revisados por pares) nesse período de tempo. 80 Essa fração de tamanho dos plásticos tem fundamentalmente duas naturezas, a primária que são os plásticos virgens (pellets) e a secundária que são os fragmentos resultantes da degradação física, química e biológica de itens maiores.…”
Section: Plásticos E Seus Poluentes Associadosunclassified
“…Ambos os tipos oferecem os mesmos riscos ao ambiente marinho e sua biota: possibilidade de ingestão que leva a danos físicos 78 e contaminação por poluentes orgânicos a eles (pré e/ou pós) associados. 79 A maior parte da literatura internacional, incluindo trabalhos desenvolvidos no Brasil, trata dos microplásticos relatando sua presença nos diferentes compartimentos ambientais 53,58,68 dentre eles a biota marinha. 52,73,74,76 Apenas recentemente houve trabalhos que começaram a investigar a associação entre plásticos e poluentes orgânicos 77 buscando testar através de experimentos controlados, esse vínculo anteriormente suposto na literatura internacional.…”
Section: Plásticos E Seus Poluentes Associadosunclassified
See 1 more Smart Citation